Increased Risk for Intracranial Arterial Stenosis in Subjects With Coronary Artery Calcification - Oh, Hyung-Geun; Chung, Pil-Wook; Rhee, Eun-Jung (Stroke (1970), 2015)
BACKGROUND AND PURPOSE—Intracranial arterial stenosis (ICAS) is considered an important cause of stroke in Asians. Coronary artery calcification (CAC) is a surrogate marker for subclinical atherosclerosis. We aimed to analyze the association of ICAS assessed by transcranial Doppler ultrasonography and CAC in middle-aged Korean population. METHODS—This study included 10 550 participants (81.3% men, mean age 43 years) from a health screening program, in whom transcranial Doppler ultrasonography was used to detect >50% intracranial stenosis based on criteria modified from the stroke outcomes and neuroimaging of intracranial atherosclerosis trial. Multidetector computed tomography was used to assess coronary artery calcium score (CACS). CAC grade (0, 1−100, and >100) was defined by CACS. RESULTS—The subjects with CAC showed significantly higher proportion of subjects with ICAS compared with those without CAC (4.4% versus 2.8%; P<0.01). Conversely, the subjects with ICAS showed significantly higher proportion of subjects with CAC (24.8% versus 17.1%; P<0.01). When logistic regression analysis was performed with ICAS as the dependent variable, the presence of CAC showed significantly increased risk for ICAS after adjustment for confounding variables (odds ratio, 1.439; 95% confidence interval, 1.095–1.891). When CACS grade was included in the model, the odds ratio for ICAS was the highest in subjects with CACS >400 compared with those with CACS=0 (odds ratio, 2.754; 95% confidence interval, 1.205–2.936). CONCLUSIONS—The risk for ICAS was significantly increased in middle-aged Korean subjects with CAC compared with that in those without CAC. These findings suggest the possibility of a separate undetected atherosclerotic focus in subjects with 1 atherosclerotic event.